Consumer-Side Decision Factors on Their Selection of Bottled Water Brands: Statistical Method Study in a Kosovo Sample - Kajtazi, Saranda (Ekonomika, 2018)
Nowadays, to meet people’s needs in daily life for drinking water, many companies provide bottled drinking water. As this industry grows and more competition occurs, the companies should know the aspects that influence people to buy the products that are bottled drinking water. Although this increase in several bottled water producers can be attributed to market demand and technology modernization, the fact that consumers migrate from one brand to another is significant and indicates that there are factors that affect the consumer’s decision when choosing the bottled water brand. The aim of this paper is to identify and analyze the factors that influence consumers the most when choosing a bottled water brand in the market, using Kosovo as a case study. To define factors based on the consumer’s preferences and valuations of the importance, the principal component analysis was applied based on a correlation matrix, using a component extraction method with a varimax rotation and a Kaiser-Meyer-Olkin adequacy test. The findings show that the consumer’s decision is influenced mostly by six key factors, namely quality, marketing, consumer perception, price, preference and practicality. The research provides new insights into the bottled water manufacturing industry and marketers in positioning themselves in a competitive environment.